Electronic government procurement adoption behavior amongst Malaysian SMEs - Yusoff, Wan Yusoff; Abas, Zakaria; Md. Aminul, Islam; Muhd Yusuf, Dayang Hasliza (Canadian Center of Science and Education (CCSE), 2011)
The aim of this study is to investigate the relationship between a model of electronic procurement (e-procurement) adoption behavior and the level of Government e-procurement adoption amongst Small Medium Enterprise (SME) in Malaysia. Data was collected through questionnaires that were distributed to SME selected randomly in all SME in Malaysia.The data were analyzed using factor analysis, reliability analysis, independent-sample t-test, descriptive statistics, Pearson Correlation and multiple regressions. Regression results reveals that ‘power’, ‘trust’ and ‘value’ have a positive relationship with the level of e-procurement adoption amongst SME in Malaysia.All dimensions, namely; the power of supplier, power of procurement, trust on supplier, trust on information technology, value of implementation system efficiency and value of cost efficiency were also correlated with the level of e-procurement adoption amongst SME. Past studies on e-procurement are beset by problems of buyer-seller relationship perspective.In addition, these studies are skewed towards Government-SME relationship perspective which the Government possesses more power than SME and provide a better incentive to educate and influence SME to adopt e-procurement.In investigation the relationship between a model of e-procurement adoption behavior and the level of Government e-procurement adoption amongst SME in Malaysia, this study also tries to provides recommendation to Malaysian government for improving the level of e-procurement adoption amongst SME.